Analisis Kesiapan Sumber Daya Manusia dalam Penerapan Rekam Medis Elektronik Di Puskesmas Se-Kecamatan Banjarmasin Tengah - Susanti Ernawati; Muhammad Rashif Anshari; Fatmawati Bakri Noor; Galih Persadha (UPPM Politeknik Unggulan Kalimantan, 2024)
Human Resources (HR) play a crucial role in the operation of any company or organization. The medical records unit is a key supporting organization within healthcare facilities, requiring high performance and meticulous attention from its staff. A preliminary study conducted on February 2, 2024, in five Community Health Centers (Puskesmas) in the Banjarmasin Tengah District—namely Puskesmas S. Parman, Puskesmas Sungai Mesa, Puskesmas Gedang Hanyar, Puskesmas Teluk D, and Puskesmas Cempaka Banjarmasin—revealed through interviews with the heads of the medical records departments that while these centers have implemented Electronic Medical Records (EMR), several challenges remain. These challenges include a lack of understanding among staff about EMR, errors in patient medical record data entry, misfiling, inadequate training, and staff lacking educational background This research employs a qualitative method with a descriptive approach, using observation guidelines, interview guidelines, and questionnaires as tools for data collection. The findings indicate that from the perspective of human resource quality, the staff is not yet prepared to support the implementation of electronic medical records because they have not received training on EMR, and many do not have a background in medical records. In terms of quantity, there are 17 medical records staff across the five Community Health Centers in Banjarmasin Tengah District, averaging three medical records staff per center. It is recommended that future hiring for medical records positions in the Community Health Centers within Banjarmasin Tengah District prioritize candidates with educational backgrounds in medical records and health information to enhance the quality.